A nonbehavioral theory of saving - Michalis Nikiforos (Levy Economics Institute of Bard College, 2015)
We present a model where the saving rate of the household sector, especially households at the bottom of the income distribution, becomes the endogenous variable that adjusts in order for full employment to be maintained over time. An increase in income inequality and the current account deficit and a consolidation of the government budget lead to a decrease in the saving rate of the household sector. Such a process is unsustainable because it leads to an increase in the household debt-to-income ratio, and maintaining it depends on some sort of asset bubble. This framework allows us to better understand the factors that led to the Great Recession and the dilemma of a repeat of this kind of unsustainable process or secular stagnation. Sustainable growth requires a decrease in income inequality, an improvement in the external position, and a relaxation of the fiscal stance of the government.
Keywords: E12; E21; E32; E60; 330; Inequality; Financial Balances; Saving; Secular Stagnation; Sustainability